RELACIONES PÚBLICAS 2.0 (Y EDUCOMUNICACIÓN). ¿DE QUÉ HABLAMOS REALMENTE? UN ACERCAMIENTO CONCEPTUAL Y ESTRATÉGICO* - Carmen SILVA ROBLES,Rodrigo ELÍAS ZAMBRANO (Fonseca, Journal of Communication, 2023)
It is a fact that since Web 2.0 has putting an appearance, the concept or Public Relations (PR) has been revolutionized to change even its name, being called from then on PR 2.0. Internet means new ways of Public Relations In the present study aims to look at the reality of PR 2.0 and Public Relations in the 21th century, describing how they are, and identifying which aspects make them different from traditional Public Relations. Also making an analysis of its characteristics through the proposal of Fanta “Robertus”